Profile of Learners Argumentation Ability on Socio-Scientific Issues - Fauziah, Siva; Hernawati, Diana; Rizal, Rahmat; Badriah, Liah (Jurnal Pijar Mipa, 2025)
This study aims to determine the profile of students' argumentation skills at MTs Idrisiyyah, Tasikmalaya Regency, in the context of Socio-Scientific Issues (SSI), which includes issues related to science and society based on the components of scientific argumentation from the Toulmin model. The study used a quantitative descriptive method; as many as 63 Grade VIII learners participated. The results of the analysis showed that the ability to claim was excellent (86%), but argumentation support such as data (64%), warrant (32%), qualifier (30%), and backing (27%) was still low. This finding indicates that although learners can convey claims well, they have difficulty supporting these claims with strong data and arguments. The results of this study are expected to be a reference for educators in designing more effective learning strategies related to the development of argumentation skills in the context of SSI.